Effect of ambient conditions in friction surfacing - Hoffmann, Marius; Antunes Duda, Eduardo; Aspes, Pietro; Klusemann, Benjamin (Medien- und Informationszentrum, Leuphana Universität Lüneburg, 2026)
Friction surfacing (FS) is a solid-state deposition process in which layers are deposited on a substrate surface by frictional heat and severe plastic deformation of a consumable stud material below its melting temperature. Bonding occurs due to accelerated diffusion. The deposition of several layers on top of each other is referred to as multi-layer FS (MLFS), a promising candidate for additive manufacturing (AM) as it offers advantages over fusion-based AM. In this study, the MLFS process for the precipitation-hardenable alloy AA2024 is investigated regarding the influence of environmental process conditions, i.e., preheating of the substrate like other AM processes as well as underwater and room temperature experiments. The influence of ambient conditions on the process behavior, the layer geometries, the microstructure, and the mechanical properties is shown. Preheating the substrate leads to an overall higher process temperature (424.1 °C), resulting in thinner and wider layers, larger grains, an overaged microstructure, and a smooth hardness transition in the MLFS stacks from top (140 HV0.1) to bottom (95 HV0.1). The lower the process temperatures, e.g., for underwater FS (326.5 °C), the thicker and less wide the layers and the smaller the grains. The hardness shows a periodic pattern at the layer interface, which is more pronounced at lower process temperatures, i.e., the hardness values range from 100 HV0.1 to 150 HV0.1.
Keywords: Friction Surfacing; Preheating; Underwater; Microstructure; Precipitate; Hardness